Logistic Support for the Omnichannel Strategy in the Fashion Retail – Areas and Directions of Improvement - Joanna DROBIAZGIEWICZ (Communications of International Proceedings, 2020)
The aim of the article is to present the areas of logistic support of omnichannel strategy in the fashion retail and to indicate the directions of its development. The article uses the method of critical analysis of source literature and case study.  Based on a critical analysis of the literature, the first part of the article presents the essence of the omnichannel strategy and defines the role of logistics in its implementation. Logistic support for the omnichannel strategy involves many activities, both in the area of stationary sales and e-commerce. It requires the introduction of system solutions, which concern the management of the entire supply chain both in terms of goods flows as well as the accompanying information and funds. These solutions should ensure flexibility of operation, speed of reaction and customization, which is particularly characteristic of the fashion industry strategy. In the next part of the article theoretical considerations have been referred to practical logistic solutions used in implementation of omnichannel strategy in the fashion sector. The areas of logistical support and solutions applied in these areas were defined. Next, possible directions of their improvement were indicated. Finally, there have been presented the conclusions drawn from the performed research.
Keywords: e-commerce; omnichannel; logistic support